Mission awakening in the Dutch Reformed Church: The possibility of a fifth wave? - Benadé, Christo R. (HTS teologiese studies, 2019)
The Dutch Reformed Church (DRC) had a strong missionary DNA since the planting of the church. This missionary focus and fervour, however, ebbed and flowed during the history of the church. Saayman described that the mission upsurges in the DRC in four waves or ‘periods of extraordinary mission endeavour’. The current research aimed to develop this theory through a literature study on the sociopolitical context and the developments in the ecclesiology and missiology of the DRC since the planting of the church up to 2013. The research found strong evidence to define a fifth wave. The fifth wave was influenced by contextual changes (e.g. a secularising, a more integrated multicultural society and the realisation of the needs of the poor) and loss of influence and money by the DRC. Furthermore, the growth in the church’s missional identity can be seen in the following aspects: the influence of theologians like Lesslie Newbigin and David Bosch; a belief that mission is not something the church does but something the church is; a shift from a Christocentric theology to a Trinitarian theology; a holistic view of salvation; a commitment to the local context of the congregation and a focus on bringing healing to their local communities; and lastly, the success of the Gestuurde Gemeentes network and, more recently, the Mission Shaped Ministry training.